2004
DOI: 10.1038/sj.ijo.0802615
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the relationship between lipid CHD risk factors and body composition in Caucasians and Japanese

Abstract: OBJECTIVES: To examine differences in the relationship between fat distribution and lipid coronary risk factors in Caucasian and Japanese population and further to determine whether the cut-points for body mass index (BMI) and waist circumference (WC) proposed by WHO and NHLBI are applicable to Japanese population as a predictor of a lipid risk factor abnormality or not. RESEARCH METHODS AND PROCEDURES: Subjects were 895 participants of the Baltimore Longitudinal Study of Aging in the US (BLSA) and 1705 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…Levels of HDLcholesterol in the Japanese population are higher than those reported in Caucasian populations [4,5]. This favorable lipid profile may be one of the explanations for the lower morbidity of CHD in Japanese populations [6].…”
Section: Introductionmentioning
confidence: 76%
“…Levels of HDLcholesterol in the Japanese population are higher than those reported in Caucasian populations [4,5]. This favorable lipid profile may be one of the explanations for the lower morbidity of CHD in Japanese populations [6].…”
Section: Introductionmentioning
confidence: 76%
“…WHO Expert Consultation suggested lower BMIs cut-off point at 23 for overweight in Asian population, in comparison to western BMI cut-off points for overweight (BMI ≥ 23 kg/m 2 ) [25]. A study reported that this lowered BMI as a cut-off point for overweight in Asian population was suitable because this BMI value is significantly associated with risks of chronic diseases [26]. …”
Section: Discussionmentioning
confidence: 99%
“…9,21 Alternatively, it has been suggested to use waist circumference as a better predictor of disease risk than BMI within populations. 4,22 In the study by Iwao et al 13 Japanese subjects had smaller BMI and waist circumference but worse total and low-density lipoprotein-cholesterol levels compared with Caucasians. 13 In our study, Irish subjects had (or tended to have) higher blood lipids compared with Spanish or Icelandic subjects, but in contrast to the above study, increased waist circumference in the Irish subjects explained much of the unfavorable cardio-metabolic risk profile.…”
Section: Discussionmentioning
confidence: 99%
“…4,22 In the study by Iwao et al 13 Japanese subjects had smaller BMI and waist circumference but worse total and low-density lipoprotein-cholesterol levels compared with Caucasians. 13 In our study, Irish subjects had (or tended to have) higher blood lipids compared with Spanish or Icelandic subjects, but in contrast to the above study, increased waist circumference in the Irish subjects explained much of the unfavorable cardio-metabolic risk profile. It is known that increased visceral fat negatively affects metabolic profiles by releasing free fatty acids and adipokines and as a consequence it increases diabetes and heart disease risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation